Kegiatan Pengabdian Masyarakat Mengenai Pencegahan Anemia Melalui Penapisan Hemoglobin dan Hematokrit pada Usia Dewasa di SMP Kalam Kudus 2 Jakarta - Fadil Hidayat; Alexander Halim Santoso; Edwin Destra; Hans Sugiarto; Linginda Soebrata (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
Anemia is a hematological disorder that is often not recognized in the adult age group. One lifestyle factor that can affect hemoglobin and hematocrit levels is the consumption of tea or coffee with meals, because the tannin and polyphenol content inhibits the absorption of non-heme iron. Early detection of hemoglobin and hematocrit levels accompanied by education about eating and drinking habits is an important strategy in preventing anemia. This screening activity is carried out using the Plan-Do-Check-Act (PDCA) approach. Examination of hemoglobin and hematocrit levels is carried out using Point-of-Care Testing (POCT) from capillary blood. Education is provided to all participants through leaflets and group counseling regarding the effect of tea and coffee consumption on iron absorption. A total of 91 participants took part in this activity, consisting of 39.6% men and 60.4% women, with an average age of 47.4 years. The average hemoglobin was recorded at 11.2 ± 1.6 g/dL and hematocrit at 33.0 ± 4.7%. As many as 42.9% of participants experienced anemia based on hemoglobin levels below normal values ​​according to gender. Hemoglobin and hematocrit examinations successfully identified a significant proportion of individuals at risk of anemia. Education on the right time to consume tea or coffee and increasing consumption of foods rich in iron and vitamin C are preventive interventions that can be applied to maintain optimal hematological status. Keywords: Hemoglobin, Hematocrit, Anemia, Iron, Tea, Coffee, Diet